Dlaczego potrzebujemy nowej ustawy o humanitarnej ochronie zwierząt? - Rudy, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Legal regulations concerning animals protection clearly state that man owes to respect the animal and each animal requires humane treatment that must be understood by taking into account the needs and protection of animals, as far as care providing. Systematic law amendments, which are concerned to protect the animals from suffering, including unjustified or inhumane killing or cruelty to animals, should be considered as the duty of state authorities. In particular it should be done due to taking into account that animals are recognized as the “subjects of law”, for which there is a special legal regime determined by the provisions devoted to the humanitarian animals protection.
Keywords: prawna ochrona zwierząt